Does Incremental Positioning (Weight Shifts) Reduce Pressure Injuries in Critical Care Patients?. Issue 4 (July 2017) - Krapfl, Lee Ann; Langin, Julia; Pike, Caitlin A.; Pezzella, Patricia
Abstract : BACKGROUND: Incremental positioning or weight shifts are often suggested as an alternative to standard repositioning/turning in critical care patients deemed clinically unstable. OBJECTIVE: This evidence-based report card reviews whether incremental positioning and/or weight shifts reduce hospital-acquired sacral/buttocks pressure injuries in critical care patients deemed too unstable to turn. METHODS AND SEARCH STRATEGY: A scoping review of the literature was conducted for studies related to repositioning and hospital-acquired pressure injuries in high-risk, critical care patients. The databases searched were CINAHL, EMBASE, and PubMed. Key words used in the search were "intensive care, " "critical care, " "pressure ulcer(s), " "pressure injury(ies), " "pressure sore(s), " "turn(s), " "turning, " "shift(s), " "shifting, " "position(s), " OR "positioning, cardiopulmonary support." The search yielded 183 articles. The search was then narrowed to those published within the past 10 years, yielding 35 citations. Following title and abstract review, 5 studies were identified that met inclusion criteria; an additional 13 articles were found by ancestry and hand-searching. FINDINGS: No evidence was identified that incremental positioning and/or weight shifts reduce hospital-acquired sacral/buttocks pressure injuries in critical care patients deemed too unstable to turn. In addition, no evidence was found that incremental positioning and/or weight shifts affect interface pressure on the sacrum/buttocks. However, there was evidence that incremental positioning and/or weight shifts do impact gravitational equilibrium. CONCLUSION: Despite the paucity of evidence, incremental positioning and/or weight shifts are recommended as an intervention in critical care patients deemed too unstable to turn. Further research is needed to examine whether incremental positioning and/or weight shifts are effective in reducing pressure injuries in critical care patients.